"Method and meaning": Storytelling as decolonial praxis in the psychology of racialized peoples. (August 2021) - Samuel, Cara A.; Ortiz, Drexler L.
Abstract: In psychology, there is a growing recognition of how racialized groups are often dehumanized and pathologized, and how racist and colonial legacies still inform our research and practices today. In order to dismantle racism within academic institutions we must decolonize and indigenize psychological science. One promising strategy is the use of storytelling methodology wherein participants from racialized groups share their lived experiences. However, the process of how storytelling contributes to decolonization is rarely explained, and decolonization is rarely defined. The present paper systematically reviewed studies that examined racialized individuals' lived experience using storytelling methodology in order to synthesize conceptualizations of decolonization and of how storytelling contributes to decolonizing psychological research. Findings suggest storytelling meaningfully contributes to decolonial praxis in psychology. Researchers must work consciously and collaboratively, center research around liberating racialized communities, and explicitly define how their study decolonizes in order to be accountable to their community of study and to the colonial history of the lands on which they're situated. Highlights: Western psychological research uses methods that perpetuate colonialism and racism. Researchers must work to decolonize and indigenize research with racialized groups. Storytelling is a decolonizing method that honors Western and indigenous knowledge. Decolonization must be explicitly defined by researchers to promote accountability. Researchers should collaborate with racialized communities in all research stages.